DESCRIPTION OF NEW SPECIES OF SCORPIONS Compsobuths iraqnsis, (ARACHNIDA : BUTHIDAE) FOR THE FIRST TIME IN IRAQ AND WORLD - Al-Azawii, Z. N. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
A new species of the scorpions Compsobuthus iraqensis sp.nov , was described for the first time in Iraq and world which is collected from Salahuddin governorate in Iraq .This species are characterized by pedipalps and chela are very thin and very long,the sixth segments of metasoma are very tall and less in width.The body color and legs are yellowish except the end of acelus is radish ,the total length between 26-40 mm, and the rows of granules on the movable finger of pedipalp have 10 rows,The Compsobuthus. iraqensis sp. nov. is almost similar to the species Compsobuthus. persicus,(11) from Iran, which it differed by some characters , Internal granules in all rows on the movable finger of pedipalp and in the number of granular in the metasoma segment. This study for the first time is described and recorded this species.